1978
DOI: 10.1042/bj1760295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucagon and N6O2′-dibutyryladenosine 3′:5′-cyclic monophosphate on calcium transport in isolated rat liver mitochondria

Abstract: 1. The administration of glucagon to fed rats by intraperitoneal injection, or the perfusion of livers from fed rats with glucagon by the method of Mortimore [Mortimore (1963) Am.J. Physiol. 204, 699--704] was associated with increases of 15- and 5-fold respectively, in the time for which a given load of exogenous Ca2+ is retained by mitochondria subsequently isolated from the liver. This effect of glucagon was (a) also induced by N6O2'-dibutyryl cyclic AMP, (b) completely blocked by cycloheximide, (c) relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…The cells were then suspended in 2 ml sucrose-HEPES-EGTA medium and homogenized for 60 s at setting 2-5 using an Ultra-Turrax TP ION homogenizer. Control experiments, similar to those described by Hughes & Barritt (1978), showed that the inclusion of 0-5 mM-EGTA in the isolation medium prevents the uptake of endogenous 45Ca by mitochondria. Subcellular fractions were isolated by centrifugation of: the homogenate at 200 g for 5 min (the precipitate was discarded), the supernatant from the previous step at 4600 g for 5 min (the precipitate = the mitochondrial fraction), the supernatant from the mitochondrial precipitate at 15,600 g for 10 min (the precipitate, an intermediate fraction, was discarded), and the supernatant from the previous step at 70,000 g for 90 min (the precipitate = the microsomal fraction).…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…The cells were then suspended in 2 ml sucrose-HEPES-EGTA medium and homogenized for 60 s at setting 2-5 using an Ultra-Turrax TP ION homogenizer. Control experiments, similar to those described by Hughes & Barritt (1978), showed that the inclusion of 0-5 mM-EGTA in the isolation medium prevents the uptake of endogenous 45Ca by mitochondria. Subcellular fractions were isolated by centrifugation of: the homogenate at 200 g for 5 min (the precipitate was discarded), the supernatant from the previous step at 4600 g for 5 min (the precipitate = the mitochondrial fraction), the supernatant from the mitochondrial precipitate at 15,600 g for 10 min (the precipitate, an intermediate fraction, was discarded), and the supernatant from the previous step at 70,000 g for 90 min (the precipitate = the microsomal fraction).…”
Section: Methodsmentioning
confidence: 81%
“…The respiratory control ratio (the ratio of the ADP-stimulated to ADP-depleted rates of oxygen utilization) of mitochondria prepared from isolated hepatocytes was found to be 3'0 + 0 5 (n = 19) when measured in the presence of 12-5 mM-succinate as described by Hughes & Barritt (1978). 4"Ca exchange by isolated mitochondria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another factor was the further reduction of calcium due to the inclusion of EGTA in the homogenization medium to prevent calcium re-uptake during mitochondrial isolation. Treatment of liver mitochondria with EGTA or EDTA has been shown to markedly decrease the calcium content [ 14,151.…”
Section: Resultsmentioning
confidence: 99%